Between justice and stability the politics of war crimes prosecutions in post-Milosevic Serbia - Ostojic, Mladen (Southeast European studies, 2014)
Exploring the impact of the International Criminal Tribunal for the former Yugoslavia (ICTY) on regime change in Serbia, this book examines the relationship between international criminal justice and democratisation.